Using Urban Vegetation to Reduce Airport Noise: An Eco-Friendly and Economical Solution - Putra, Dimas Endrawan; Dewantoro R, Daniel; Prayitno, Hadi; Rubiono, Gatut; Kuncoro, Wisnu (PT Inovasi Pratama Internasional, 2024)
This study investigated the effectiveness of three types of urban plants Pucuk Merah, Cemara Kifan, and Furing as noise barriers around airports. Using a 2-inch diameter sound tunnel along 6 meters with 3 mm PVC material, noise measurements were made at several points along the tunnel. The results showed that Furing plants had the most significant decrease in noise levels with an average noise reduction percentage of 46.79%. Pucuk Merah and Cemara TFan showed noise reductions of 29.54% and 23.94% respectively. Without the plant barrier, noise was only reduced by 17.77%. The characteristics of thick and dense leaves, as well as the complex structure of the plant, make Furing the most effective noise barrier. These results suggest that the use of plants, particularly furing, as a natural barrier around airports can significantly reduce the negative impact of noise and create a more comfortable environment.